Cerium Ion Mobility and Diffusivity Rates in Perfluorosulfonic Acid Membranes Measured via Hydrogen Pump Operation. Issue 12 (21st September 2017) - Baker, Andrew M.; Babu, Siddharth Komini; Mukundan, Rangachary; Advani, Suresh G.; Prasad, Ajay K.; Spernjak, Dusan; Borup, Rod L.
Abstract : Ion mobility and diffusivity coefficients were determined for cerium ions in Nafion XL perfluorosulfonic acid ionomer membranes at 100% and 50% relative humidity in a conductivity cell using a hydrogen pump. Ce ion migration profiles were quantified as a function of charge transfer through the cell using X-ray fluorescence (XRF). In order to decouple simultaneous effects of Ce ion mobility and back-diffusion which occur due to potential and concentration gradients, respectively, a one-dimensional model was developed and fit to these intermittent XRF profiles. The resulting mobility and diffusivity coefficients demonstrate the dramatic effects of potential and concentration gradients on Ce ion migration during PEM fuel cell operation.